Status of low-energy accelerator-based BNCT worldwide and in Argentina - Cartelli, Daniel Enrique (2020)
Existing and active low-energy Accelerator-Based BNCT programs worldwide will be reviewed and compared. In particular, the program in Argentina will be discussed which consists of the development of an Electro-Static-Quadrupole (ESQ) Accelerator-Based treatment facility. The facility is conceived to operate with the deuteron-induced reactions 9Be(d,n)10B and 13C(d,n)14N at 1.45 MeV deuteron energy, as neutron sources. Neutron production target development status is specified. The present status of the construction of the new accelerator development laboratory and future BNCT centre is shown.